Design, synthesis, and antiviral activity of phenylalanine derivatives as HIV-1 capsid inhibitors. (15th October 2021) - Li, Jing; Jiang, Xiangyi; Dick, Alexej; Prakash Sharma, Prem; Chen, Chin-Ho; Rathi, Brijesh; Kang, Dongwei; Wang, Zhao; Ji, Xiangkai; Lee, Kuo-Hsiung; Cocklin, Simon; Liu, Xinyong; et al.
Graphical abstract: Novel phenylalanine derivatives were identified as HIV-1 capsid inhibitors. Abstract: The HIV-1 Capsid (CA) is considered as a promising target for the development of potent antiviral drugs, due to its multiple roles during the viral life cycle. Herein, we report the design, synthesis, and antiviral activity evaluation of series of novel phenylalanine derivatives as HIV-1 CA protein inhibitors. Among them, 4-methoxy- N -methylaniline substituted phenylalanine (II-13c ) and indolin-5-amine substituted phenylalanine (V-25i ) displayed exceptional anti-HIV-1 activity with the EC50 value of 5.14 and 2.57 μM respectively, which is slightly weaker than that of lead compound PF-74 (EC50 = 0.42 μM). Besides, surface plasmon resonance (SPR) binding assay demonstrated II-13c and V-25i prefer to combine with CA hexamer rather than monomer, which is similar to PF-74. Subsequently, molecular dynamics simulation (MD) revealed potential interactions between representative compounds with HIV-1 CA hexamer. Overall, this work laid a solid foundation for further structural optimization to discover novel promising HIV-1 CA inhibitors.